APPLICATION OF COOPERATIVE LEARNING TYPES OF NON EXAMPLES EXAMPLES TO IMPROVE CRITICAL THINKING ABILITY AND STUDENT LEARNING ACHIEVEMENTS (Study on Class XI IPS Students at SMA 1 Tebing Tinggi) - Nia Sariani; Bambang Sahono (UNIB Press, 2018)
This study aims to describe the application of cooperative learning models for examples of non-examples to improve critical thinking skills and student achievement on geography subjects in class XI IPS in SMA 1 Tebing Tinggi. This research was conducted using the Classroom Action Research method, with procedures for planning, implementing, observing and reflecting. The subjects of this study were students of class XI IPS at SMA 1 Tebing Tinggi, which numbered 25 students consisting of 7 men and 8 women. Data collection techniques used are observation and test sheets. Data were analyzed by statistics, namely mean (mean) and t-test. The results of the study concluded that the application of cooperative learning models of examples of non-examples types can improve critical thinking skills and student learning achievement on geography subjects in class XI IPS in SMA 1 Tebing Tinggi.